STRUCTURAL ANALYSIS OF A STEEL COLUMN EXPOSED TO A LOCALIZED FIRE (Advances in Civil and Architectural Engineering, 2021)
This paper presents an investigation on the structural analysis of a steel column exposed to a localized fire. Because EN 1991-1-2 does not provide a simplified method to calculate heat transfer to vertical elements, a CFD (Computational Fluid Dynamics) model of a localized fire is developed, based on previously conducted experiments. Furthermore, a heat transfer analysis was performed based on the results of CFD modeling and for the ISO temperature–time curve. Finally, a nonlinear structural analysis of the steel column was conducted for the localized fire scenario, as well as for the ISO temperature–time curve. A comparison between the localized fire and ISO fire exposure points indicates that localized fires can cause earlier failure of a column, depending on the level of external load.